2023
DOI: 10.3389/fmicb.2023.1152187
|View full text |Cite
|
Sign up to set email alerts
|

Solar radiation explains litter degradation along alpine elevation gradients better than other climatic or edaphic parameters

Abstract: Organic matter (OM) decomposition has been shown to vary across ecosystems, suggesting that variation in local ecological conditions influences this process. A better understanding of the ecological factors driving OM decomposition rates will allow to better predict the effect of ecosystem changes on the carbon cycle. While temperature and humidity have been put forward as the main drivers of OM decomposition, the concomitant role of other ecosystem properties, such as soil physicochemical properties, and loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Previous studies confirmed the suitability of this approach in terms of the representativeness of experimental comparisons of local litter with teabag decomposition dynamics [71,72]. As previously demonstrated by Didion et al [71], we confirmed the slowest decomposition rate at the alpine level and also that rooibos tea degraded slower than green tea [38]. In alpine environments, microtopography can play a decisive role in the spatial distribution of different humus systems and forms [73,74].…”
Section: Alpine Meadows: Humus Homogeneity and Organic Matter Accumul...supporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies confirmed the suitability of this approach in terms of the representativeness of experimental comparisons of local litter with teabag decomposition dynamics [71,72]. As previously demonstrated by Didion et al [71], we confirmed the slowest decomposition rate at the alpine level and also that rooibos tea degraded slower than green tea [38]. In alpine environments, microtopography can play a decisive role in the spatial distribution of different humus systems and forms [73,74].…”
Section: Alpine Meadows: Humus Homogeneity and Organic Matter Accumul...supporting
confidence: 89%
“…levels, and along two opposing facing slopes (north and south), for a total of 2 regions × 2 elevations × 2 slopes × 3 replicate plots = 24 sites. Moreover, we randomly chose three replicate plots separated by at least 100 m. Plot size varied according to the vegetation type [38]: in the conifer forests of the subalpine zone, the plots' area was 400 m 2 (20 m × 20 m), whereas in the grasslands of the alpine zone, they were 25 m 2 (5 m × 5 m). For plant taxonomy we used the Flore de la Suisse [39] and the Flora Helvetica [40].…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that temperature and precipitation are key influences of plant growth and decomposer activity, root decomposition is likely to be highly responsive to variations in these two parameters (Bonato et al, 2023;Semeraro et al, 2023). In addition, the availability of nutrients and C sources influences the response of microorganisms to climate change (Sullivan et al, 2019).…”
Section: Climatic Factorsmentioning
confidence: 99%